Gossip, Humor, and the Art of Becoming an Intimate of Jesus - Capps, Donald (Journal of religion and health, 2012)
In Living Stories (Capps 1997) I addressed the rather broad consensus among clergy and laity alike that gossip is destructive of congregational life, a consensus based on the view that gossip invariably involves negatively critical conversations about other individuals and groups. However, this view is not supported by social scientific research and literary studies on gossip, which present a more complex picture of this form of human communication. On the other hand, the claim that gossip is trivial is more difficult to challenge, so I made a case for the importance of the trivial through consideration of the formal similarities between gossip and the narratives that comprise the Gospels, including the fact that both employ an "esthetic of surfaces" that focuses on specific personal particulars and that the stories that are told derive their power from the freedom that the participants in the conversation gain from entering imaginatively into the life of other persons. The present article furthers the exploration of the affinities between gossip and Gospel narratives by noting the role of humor in fostering good gossip and the mutually supportive role of gossip and humor in the art of becoming an intimate of Jesus.